Iron function and dysfunction in the brain: A pediatric neurologist's perspective - Stafstrom, Carl E. (Journal of Pediatric Biochemistry, 2012)
Iron plays a critical role in brain development and physiology, cytoplasmic protein function, and mitochondrial reactions. Brain iron levels are regulated tightly, and pathologies can result from both iron deficiency (learning and memory deficits, neuronal and dendritic developmental alterations, impaired myelin function, and abnormal neurotransmitter regulation) and iron overload (free radical production and oxidative stress, as proposed for Parkinson and Alzheimer diseases as well as rare genetic disorders of iron accumulation). This review briefly summarizes the roles of iron in normal and abnormal brain function, with emphasis on the developing brain, and describes some disorders deriving from deficient or excessive iron levels.
Keywords: Iron; brain; iron deficiency; transferrin; ferritin; aceruloplasminemia